The epics: missing links - Patni, B. (Harman Publ. House, 2009)
The passionate woman (Devayānī) -- Yayāti (The insatiable desire) -- The Lacquer house (The lacquer house of Vāraṇāvata) -- The destiny (Jarāsandha) -- An exile -- The game of dice (Nala and Damayantī) -- A Virgin's dreamchild -- The perfect man (Dharmavyādha) -- Questions and answers (The Yakṣa) -- The haunting stigma (The syamantaka gem) -- The boon (Kālayavana and Muchukunda) -- The aspiration of Uṣā -- A tryst with Kṛṣṇa -- A felicitation (an account of dhanya and āścharya)